Immature, but Not Mature, Dendritic Cells Are More Often Present in Aggressive Periodontitis Than Chronic Periodontitis: An Immunohistochemical Study - Motta, Raphael J. G. da; Tirapelli, Camila; Silva, Roberto Juns da; Villafuerte, Kelly R. V.; Almeida, Luciana Y. [UNESP]; Ribeiro-Silva, Alfredo; Leon, Jorge E. (Amer Acad Periodontology, 2016)
Background: Dendritic cells (DCs) form a key link between innate and adaptive immune responses. The aim of this study is to analyze presence and distribution of immature (im) and mature (m) DCs in gingival tissue samples obtained from patients diagnosed with aggressive periodontitis (AgP), chronic periodontitis (CP), and clinically healthy periodontium (control group). Methods: Gingival tissue samples obtained from patients with: 1) AgP (aged <35 years); 2) CP (aged >= 35 years); and 3) control group (aged > 18 years) (n = 10 per group) were collected. Two-way analysis of variance and posterior Fisher least significant difference test were used to observe differences between the means of cells positively marked for imDC (S100, CD1a, and CD207) and mDC (CD208) immunomarkers. Results: imDCs were more numerous in AgP than CP and control groups, being statistically significant only for S100+ cells. Conversely, mDCs were visualized in higher numbers in CP than AgP and control groups (both P <0.05). Considering frequency of immunostained cells, the number of S100+ cells was greater than CD207+ and CD1a+ cells, followed by a lesser number of CD208+ cells, in all groups. Conclusions: Considering that the ability of DCs to regulate immunity is dependent on DC maturation, results suggest that predominance of imDCs appears to be involved in AgP pathogenesis, probably due to lack of ability to induce immune cell activation. Further studies are necessary to elucidate the role of DC maturation in regulating immune responses in periodontal disease.
Keywords: Aggressive periodontitis; immunology; oral pathology